Persistence and generalization of adaptive changes in auditory localization behavior following unilateral conductive hearing loss - Sanchez Jimenez, Ana; Willard, Katherine J.; Bajo, Victoria M.; King, Andrew J.; Nodal, Fernando R. (Frontiers in Neuroscience, 2023)
Sound localization relies on the neural processing of binaural and monaural spatial cues generated by the physical properties of the head and body. Hearing loss in one ear compromises binaural computations, impairing the ability to localize sounds in the horizontal plane. With appropriate training, adult individuals can adapt to this binaural imbalance and largely recover their localization accuracy. However, it remains unclear how long this learning is retained or whether it generalizes to other stimuli. We trained ferrets to localize broadband noise bursts in quiet conditions and measured their initial head orienting responses and approach-to-target behavior over repeated periods of monaural earplugging that were interleaved with short or long periods of normal binaural hearing. A smaller initial deficit was observed when the same ear was occluded on three subsequent occasions, and each time the animals’ performance recovered with training to near pre-plug levels of localization accuracy. By contrast, switching the earplug to the contralateral ear resulted in less adaptation, indicating that the capacity to learn a new strategy for localizing sound is more limited if the animals have previously adapted to conductive hearing loss in the opposite ear. To explore learning generalization to other stimulus types, we also measured localization accuracy before and after adaptation using different bandwidth stimuli presented against constant or amplitude-modulated background noise. The degree of adaptation for individual animals was significantly correlated with the extent to which learning extended to untrained octave band target sounds presented in silence and to broadband targets presented in background noise, suggesting that adaptation and generalization go hand in hand. Together, these findings provide further evidence for plasticity in the weighting of monaural and binaural cues during adaptation to unilateral conductive hearing loss, and show that the training-dependent recovery in spatial hearing can generalize to more naturalistic listening conditions, so long as the target sounds provide sufficient spatial information.